2015
DOI: 10.1016/j.scitotenv.2014.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Pepper mild mottle virus as an indicator and a tracer of fecal pollution in water environments: Comparative evaluation with wastewater-tracer pharmaceuticals in Hanoi, Vietnam

Abstract: We analyzed pepper mild mottle virus (PMMoV) in 36 samples taken from surface water, wastewater, groundwater, tap water and bottled water in Hanoi, Vietnam. We then compared the occurrence and fates of PMMoV with pharmaceuticals and personal care products (PPCPs), which are known wastewater tracers. PMMoV was detected in 94% of the surface water samples (ponds, water from irrigated farmlands and rivers) and in all the wastewater samples. The PMMoV concentration ranged from 5.5×10(6)-7.2×10(6)copies/L in wastew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 55 publications
10
83
0
2
Order By: Relevance
“…Some researchers reported that PMMoV has the potential to be an overly sensitive marker, due to its high concentrations in human wastewater (17,32,33). While this presents an advantage for the PMMoV as a sensitive marker, its presence may also overestimate risk (23).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers reported that PMMoV has the potential to be an overly sensitive marker, due to its high concentrations in human wastewater (17,32,33). While this presents an advantage for the PMMoV as a sensitive marker, its presence may also overestimate risk (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these channels receive industrial effluents. In response to these challenges, the system was expanded in recent years to control the water flow out of the city and treat the wastewater with conventional treatment plants and decentralised water management systems (Kuroda et al, 2015). The latter should prevent flooding events, while regulating the water flow with water gates and a series of artificial ponds.…”
Section: Introductionmentioning
confidence: 99%
“…Noroviruses are selected as a reference pathogen; they are the major cause of viral gastroenteritis worldwide, with an estimated 698.8 million cases and 218,800 deaths annually [52]. The distribution of norovirus concentrations in floodwater was estimated based on the Escherichia coli concentrations simulated using the WEAP model, and the relationship between E. coli concentrations and norovirus concentrations observed in the Nhue River, which flows through Hanoi city [53,54] (this relationship was used in other cities as well). The volume of the unintentional ingestion of floodwater was estimated using the hourly inundation depths in each grid from the inundation model using Flo-2D.…”
Section: Health Risk Assessmentmentioning
confidence: 99%